Segmentation of hip cartilage in compositional magnetic resonance imaging: A fast, accurate, reproducible, and clinically viable semi‐automated methodology. Issue 8 (14th March 2018) - Fernquest, Scott; Park, Daniel; Marcan, Marija; Palmer, Antony; Voiculescu, Irina; Glyn‐Jones, Sion
ABSTRACT: Manual segmentation is a significant obstacle in the analysis of compositional MRI for clinical decision‐making and research. Our aim was to produce a fast, accurate, reproducible, and clinically viable semi‐automated method for segmentation of hip MRI. We produced a semi‐automated segmentation method for cartilage segmentation of hip MRI sequences consisting of a two step process: (i) fully automated hierarchical partitioning of the data volume generated using a bespoke segmentation approach applied recursively, followed by (ii) user selection of the regions of interest using a region editor. This was applied to dGEMRIC scans at 3T taken from a prospective longitudinal study of individuals considered at high‐risk of developing osteoarthritis (SibKids) which were also manually segmented for comparison. Fourteen hips were segmented both manually and using our semi‐automated method. Per hip, processing time for semi‐automated and manual segmentation was 10–15, and 60–120 min, respectively. Accuracy and Dice similarity coefficient (DSC) for the comparison of semi‐automated and manual segmentations was 0.9886 and 0.8803, respectively. Intra‐observer and inter‐observer reproducibility of the semi‐automated segmentation method gave an accuracy of 0.9997 and 0.9991, and DSC of 0.9726 and 0.9354, respectively. We have proposed a fast, accurate, reproducible, and clinically viable semi‐automated method for segmentation of hip MRI sequences. This enables accurate anatomical and biochemical measurements to be obtained quickly and reproducibly. This is the first such method that shows clinical applicability, and could have large ramifications for the use of compositional MRI in research and clinically. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2280–2287, 2018. Abstract : We have proposed a fast, accurate, reproducible, and clinically viable semi‐automated method for segmentation of hip MRI sequences. This method comprises (i) a fully automated hierarchical partitioning of the data volume generated using a bespoke segmentation approach applied recursively, followed by (ii) user selection of the regions of interest using a region editor. This method enables accurate cartilage measurements to be obtained quickly and reproducibly, and could have large ramifications for the use of compositional MRI in research and clinically.